2005
DOI: 10.1007/s00167-005-0633-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of posterior cruciate ligament reconstruction techniques using cyclic loading tests

Abstract: Posterior tibial translation (PTT) of the posterior cruciate ligament (PCL) reconstructed-knee under cyclic loading of 1,000 cycles with a 100-N load was compared between four different procedures, including two reconstructions with patellar tendon graft (transtunnel and inlay techniques) and two reconstructions with hamstring tendon graft (Endobutton and EndoPearl techniques) in twelve fresh-frozen human knees. The EndoPearl technique is a direct tendon fixation using biodegradable interference screws and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
(43 reference statements)
2
25
0
Order By: Relevance
“…The mechanism of the “killer turn” has been illustrated by several biomechanical studies. The excessive load at the acute bend, and repetitive friction because of non‐isometric graft placement are possible explanations of the “killer turn” effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of the “killer turn” has been illustrated by several biomechanical studies. The excessive load at the acute bend, and repetitive friction because of non‐isometric graft placement are possible explanations of the “killer turn” effect.…”
Section: Discussionmentioning
confidence: 99%
“…According to the testing protocol of previous experiments, in both groups, after the tibial side of the graft was fixed, the other end of the graft was mounted onto an MTS model‐858 Mini Bionix servohydraulic materials testing machine (MTS Systems, Minneapolis, Minnesota, USA) for the cyclic loading test. Our device employed an MTS Model 858.11 load unit that is fatigue‐rated at 100 N, with a resolution of 0.001 N. This freestanding load unit can be operated at frequencies up to 30 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Although the hamstring tendon has several advantages making it superior to a BTB graft, it also has several disadvantages. The tendon fixation to the bone is still a challenge in spite of the numerous surgical devices available [33]. Relatively slow maturation of the tendon-bone interface accentuates the need for retaining the graft firmly when the reconstructed-knee is subject to a repetitive load [34].…”
Section: Discussionmentioning
confidence: 99%
“…49,50 However, other biomechanical studies have demonstrated only small differences in graft pretension, graft forces, or knee kinematics between tibial inlay and transtibial techniques. [51][52][53][54] Moreover, recent clinical comparisons between tibial inlay and transtibial techniques have failed to demonstrate the superiority of either reconstructive technique for treating isolated PCL insufficiency in short-term to mid-term follow-up. 55,56 Using a quadrupled hamstring autograft, Seon and Song 55 compared transtibial tunnel fixation with a tibial inlay technique using BTB autograft at a minimum 2-year follow-up (level III).…”
Section: Nonoperative Managementmentioning
confidence: 97%